2008
DOI: 10.1089/thy.2008.0108
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Predictor Model for Indeterminate or Suspicious Thyroid FNA Samples

Abstract: A predictor model was created using the variables age, nodule size, and FNA cytology to predict thyroid malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
4
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 26 publications
(58 reference statements)
5
90
4
9
Order By: Relevance
“…We must note that some studies have shown a significant linear dose-response relationship over a relatively broad range of doses and a higher risk after exposure in childhood (55). Although some studies have reported a higher risk of thyroid carcinoma for TNs occurring in young people and older people with a bimodal distribution (31,45,56,57), our analysis did not show these findings. However, limitations are present in our meta-analysis for age because it is a continuous variable, and most studies presented non-uniform, aggregate data on age.…”
Section: Clinical Tn Featurescontrasting
confidence: 79%
“…We must note that some studies have shown a significant linear dose-response relationship over a relatively broad range of doses and a higher risk after exposure in childhood (55). Although some studies have reported a higher risk of thyroid carcinoma for TNs occurring in young people and older people with a bimodal distribution (31,45,56,57), our analysis did not show these findings. However, limitations are present in our meta-analysis for age because it is a continuous variable, and most studies presented non-uniform, aggregate data on age.…”
Section: Clinical Tn Featurescontrasting
confidence: 79%
“…The limited value of FNA and frozen section examination as the diagnosis was deferred in 76 (58.9%) patients in our study, several clinical factors have been investigated for their potential value in predicting carcinoma and determining the extent of thyroid surgery. While certain clinical features such as male gender and nodule size (≥4 cm), older patient age, or cytologic features such as presence of atypia can improve the diagnostic accuracy for malignancy in patients with indeterminate cytology, (18)(19)(20)(21) overall predictive values are still low and even has been reported conflicting results. (17) Recently, many potential immunohistochemical and molecular markers such as galectin-3, cytokeratin-19 (CK19), HBME-1, thyroid transcription factor 1 (TTF-1), RET/PTC gene rearrangements, and B-raf mutations have been studied to improve diagnostic accuracy for indeterminate nodules.…”
Section: Discussionmentioning
confidence: 99%
“…(16,18,19,25,26) According to the ATA guideline, initial total thyroidectomy is recommended in patients with indeterminate nodules who have large tumors (>4 cm) due to an increased risk for malignancy. Taneri et al (26) found in HCN that there was no malignancy among the tumors less than 1 cm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative distinction of benign and malignant thyroid nodules is often difficult and frequently inaccurate. The nodules that can be challenging diagnostically include the following histological subtypes: benign (follicular adenoma, adenomatoid nodule, lymphocytic thyroiditis nodule, and Hü rthle cell adenoma) and malignant (Hü rthle cell carcinoma, follicular carcinoma, follicular variant of papillary thyroid carcinoma, and papillary thyroid carcinoma) (5). Although fine needle aspiration (FNA) cytology evaluation is the most accurate means of diagnosing thyroid nodules, even experienced cytopathologists encounter problems with FNA samples for which cytological features neither confirm nor rule out malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, studies by others and our group have revealed differences in gene expression between benign and malignant thyroid tumors (10)(11)(12)(13)(14)(15)(16)(17)(18). However, no study has included all of the thyroid tumor types that have associated suspicious FNA cytology (5), nor successfully implemented them as a diagnostic adjunct to FNA in a large cohort of patients with suspicious thyroid lesions. Relevant to this, by utilizing microarray analysis, we have previously identified 75 molecular markers that are differentially expressed between benign and malignant thyroid tumors (19).…”
Section: Introductionmentioning
confidence: 99%